ANALISIS PENILAIAN FINANCIAL DISTRESS MENGGUNAKAN MODEL ALTMAN (Z-SCORE) PADA PERUSAHAAN KOSMETIK YANG TERCATAT DI BURSA EFEK INDONESIA - NIA F, HILDA Nia (Jurnal Akuntansi AKUNESA, 2012)
The purpose of this research is to know the financial performance and bankruptcy prediction at last three years using four samples of cosmetic’s firms, that is PT Unilever Tbk, PT Martina Berto Tbk, PT Mandom Indonesia Tbk, and PT Mustika Ratu Tbk.. The analysis methods in this research is bankruptcy analysis Altman z-score model with five variable. The result shows that there is no firms are predicted bankrupt, but PT Mustika Ratu Tbk and PT Martina Berto Tbk on the grey area category.Keyword : financial distress, bankruptcy, z-score Altman model.